CRITICAL PERSPECTIVES ON IDENTITY AND DISINFORMATION IN THE DIGITAL AGE - Dean Jackson (The Journal of Intelligence, Conflict and Warfare)
On November 18, 2024, Mr. Dean Jackson presented Critical Perspectives on Identity and Disinformation in the Digital Age for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed included the three eras of study and response, approaches and limitations in confronting disinformation, and implications for future research and response.